Convention of Optical Vortices in Two-Helix Long-Period Fiber Gratings - 张晓强 陈瑞山 周勇 明海 王安廷 (Chinese physics letters, 2016)
An effective method to fabricate two-helix long-period fiber gratings （TH-LFGs） is presented. Based on the coupling mode theory, the conversion of optical vortices （OVs） in TH-LFGs are analyzed in detail. The conversions of OVs with different topological charges： 0 → ±2 and 1 → 3 are simulated as three examples and the conversion efficiency higher than 98% can be realized.